Alliin as a Natural Bioactive from Single Bulb Garlic (Allium sativum) for Nitric Oxide (NO) Increasing in Atherosclerotic Process Based on Insilico Screening - Riza Rahayu Ilmawati; Ahya Zhilalikbar Amin; Mohamad Amin (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2017)
Atherosclerosis is a chronic inflammatory disease in the arterial wall mediated by proinflammatory factor. Atherosclerosis cause heart disease and stroke is generally believed to be preventable. The single bulb garlic is one of the local plants known as the medicinal plant in Indonesia. Garlic contains alliin compounds as antiatherosclerotic agent. This study aimed to determine the potential of active compound of single bulb garlic as an antioxidant that improve endothelial function by increasing nitric oxide (NO) to increase vasodilation. The bioinformatics webserver used in this study are: Pubchem, Pharmmapper, Swiss Target Prediction, Superpred, Uniprot, and Protein Data Bank. Docking software using PyRx, PyMOL and Discovery Studio. Based on these steps, it was found that alliin interacts with nitric oxide synthase (NOS) through hydrogen and alkyl bonds. Alliin is effective as an inhibitor of NOS based on binding afinity (-5.4 kcal / mol) although no more negative than an aspirin inhibitor based on binding afinity (-6.5 kcal / mol). Based on the docking results, it is found that alliin is effective as a potential drug to decreased atherosclerosis.